Sovereign Asset-Liability Management : Guidance for Resource-Rich Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
Ample natural resource revenues create both opportunities and challenges for a sovereign to transform its natural resources into well-managed financial assets. Hence, inter-temporal smoothing of revenue and consumption/investment moves to the center stage of macroeconomic policies. The questions arising from natural resource wealth accumulation are becoming more pressing for many countries, given the need to achieve intergenerational equity in a context where commodity prices may not continue their upward trajectory of the past decade. Addressing these questions requires a flexible sovereign asset-liability management (SALM) framework that integrates various macroeconomic and financial trade-offs with the aim of containing financial risk to the sovereign balance sheet. The framework and policy advice aims to guide policymakers across different institutions in weighing those trade-offs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet